Sucrose Intolerance Tests in the Neonates - Purnomo Suryantoro; Nelwan Nelwan; Ismangun Ismangun (Indonesian Pediatric Society, 1980)
Sucrose maldigestion is difficult to diagnose especially in newborn babies. Stool chromatography is the most useful tool to detect the type of saccharide maldigestion. Using the clinical symptoms as parameter, there were 3 out of 28 mabies suffering from sucrose maldigestion, in whom the blood glucose Level did not increase more than 40 mg % after the injection of sucrose.